Arabic translation and validation of pediatric lower urinary tract symptom score (PLUTSS). Issue 1 (2nd January 2023) - Al-Najar, Amr; Al-Nadhari, Ibrahim; Basabih, Sami; Alobathani, Fawaz; Akbal, Cem
ABSTRACT: Objectives: To develop and validate an Arabic version of the pediatric lower urinary tract symptom score (PLUTSS). Methods: The linguistic translation of the PLUTSS into Arabic was carried out by following the guidelines that have been set out for cross-cultural adaptation of health-related QoL measures (Translation, Reconciliation, Retranslation, Review of retranslation, Debriefing and final review). The questionnaires were applied to 80 patients, 40 patients seeking urology clinic for lower urinary tract symptoms (LUTS) and 40 patients visiting a pediatric clinic without urological compliant. The discrimination validity and strength of association were tested using Mann-Whitney and chi-square tests. Reliability of translation was tested for internal consistency using the Cronbach's α and ROC Curve was used to evaluate the ability of the questionnaire to discriminate between cases and controls. Results: Patients with LUTS had a higher PLUTSS score and QoL score than controls (P < 0.001). The value of Cronbach's alpha of the 13 items (excluding Qol) evaluated on the scale was 0.717 (95% CI: 0.616–0.800). The ROC curve determined the ability of the questionnaire to discriminate between cases and controls where the area under the curve was 0.901 (95% CI: 0.830–0.972). Conclusion: The Arabic translated version of the PLUTSS is an acceptable and reliable tool for assessing and evaluating pediatric patients with LUTS in Arabic-speaking countries.